Oil adsorbing and transporting surfaces: a simulative determination of parameters for bionic functional textiles. (1st May 2023) - Wagner, Jan; Akdere, Musa; Gürbüz, Kevser; Beek, Leonie; Klopp, Kai; Ditsche, Petra; Mail, Matthias; Gries, Thomas; Barthlott, Wilhelm
Abstract: Certain superhydrophobic plants, such as Salvinia molesta, are able to adsorb oil films from water surfaces and thus separate the oil from the water. There are first attempts to transfer this phenomenon to technical surfaces, but the functional principle and the influence of certain parameters are not yet fully understood. The aim of this work is to understand the interaction behavior between biological surfaces and oil, and to define design parameters for transferring the biological model to a technical textile. This will reduce the development time of a biologically inspired textile. For this purpose, the biological surface is transferred into a 2D model and the horizontal oil transport is simulated in Ansys Fluent. From these simulations, the influence of contact angle, oil viscosity and fiber spacing/diameter ratio was quantified. The simulation results were verified with transport tests on spacer fabrics and 3D prints. The values obtained serve as a starting point for the development of a bio-inspired textile for the removal of oil spills on water surfaces. Such a bio-inspired textile provides the basis for a novel method of oil–water separation that does not require the use of chemicals or energy. As a result, it offers great added value compared to existing methods.